Expression of iron metabolism: related genes in a portuguese population of Alzheimer’s disease patients - Cavaco Guerreiro, Cláudia (2014)
Dissertação de Mestrado em Biologia Humana e Ambiente apresentada à Faculdade de Ciências de Universidade de Lisboa, 2013.